Aesthetic Systems Theory: Doing Hip Hop Kulture Research Together at Cipher5 - MacDonald, Michael B.; Hamilton, Andre (MUSICultures, 2015)
Aesthetic Systems is an original theory to explain how aesthetic resources are made, shared and used in the formation of art works and of collective and individual subjectivities. Aesthetic systems theory has ontological, epistemological and methodological implications for the study of aesthetics, aesthetics education and the cultural studies of music, and argues for community-engaged aesthetics research. The most striking implication of aesthetic systems is the methodological requirement to undertake community-engaged critical dialogical research informed by critical pedagogy, ethnomusicology and the cultural studies traditions. This article is both the story of the intellectual partnership that built Cipher5, an Edmonton-based hip hop research/study group and an argument for the necessity of community-engaged cartographies of mediation to shed light on the relationship between the formation of subjectivities and aesthetic education. If aesthetic systems form subjectivities, how might music education programs use this knowledge to inquire after the formation of student subjectivities?